FORMATION OF FUTURE KINDERGARTEN TEACHERS’ ETHNOCULTURAL COMPETENCE IN NON-FORMAL ARTISTIC AND CREATIVE GROUPS - Sulaieva, Nataliia; Hnizdilova, Olena; Palekha, Olha (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the paper is to identify the role and place of non-formal artistic and creative groups in the process of formation of future kindergarten teachers’ ethnocultural competence. Ethnocultural competence is considered by authors as an essential component of future kindergarten teachers’ vocational training in condition of modern challenges, which Ukrainian society faces nowadays. The complex of theoretical and empirical research methods (literature analysis, interview, experiment, etc.) was used. The obtained results show positive dynamics of formation of future kindergarten teachers’ ethnocultural competence after receiving non-formal education in artistic and creative groups at higher educational institution.